THE UTILIZATION OF BIOCOAGULANT FROM MELON SEEDS POWDER TOWARDS THE DECREASE IN pH, TSS AND TDS IN TOFU INDUSTRIAL LIQUID WASTE - Euis Kusniawati; Indah Pratiwi; Dhearra Gelennea Vega Antari (Bajang Institute, 2023)
Tofu industrial liquid waste contains very high organic materials. The organic compounds in the liquid waste are in the forms of proteins, carbohydrate, fats and oil. Therefore, the tofu wastewater should go under special treatment before being disposed into the environment to reduce pollution. One alternative coagulant that can be used is melon seed powder (Cucumis melo L.). Melon seeds (Cucumis melo L.) have many benefits, one of which can function as a coagulant for wastewater treatment from tofu industry. The purpose of the study was to determine the effects of mass variations, variations of stirring and duration of deposition on the results of the coagulation and flocculation process of tofu industrial wastewater. This study used melon seed powder with low water content. Variations of coagulant mass applied in the testing were 0.3 g, 0.5 g, and 0.7 g, and the coagulant size was 80 mesh, with an initial pH of 3.5, TSS (Total Suspended Solid) 420 mg/L, and TDS (Total Dissolved Solid) 4.250 mg/L, while the optimum deposition time obtained was 30 minutes with pH changing to 5.0, TSS 199 mg/L, and TDS 1689 mg/L.